Implementing event-driven microservices architecture in .NET 7 : develop event-based distributed applications that can scale with ever-changing business demands using C# 11 and .NET 7 /: develop event-based distributed applications that can scale with ever-changing business demands using C# 11 and .NET 7. (2023) - Garverick, Joshua; McIver, Omar Dean
No abstract available